Efektivitas Literasi Digital Dan Informasi Melalui Media Sosial Facebook Tokoh Masyarakat Bagi Warga Desa Terusan - Tri Deliya Agustin; Indrawati; Jawasi (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
There are people who think that conveying information or posting news on Facebook social media is too excessive and that many or all things are put on Facebook social media. This gives rise to a bad view of the news itself. Community leaders' Facebook social media accounts were ultimately used as a forum for developing digital literacy and disseminating information for village communities. The aim of this research is to determine the effectiveness of digital literacy and information via social media Facebook of community leaders for the residents of the village of Juruan. This research method is included in quantitative research with a research design using classical assumption test data analysis techniques and multiple linear regression. Based on the results of calculating the correlation coefficient value of the three variables, it reached 0.912 or 91.2%, which proves that the dissemination of digital literacy and information through social media Facebook, community leaders for residents of the Canal village is very effective. From the results of the discussion, it can be concluded that the effectiveness of digital literacy and information via social media, Facebook, of community leaders for the residents of the Canal village exceeds 50%, where this value means that there is a very effective effect for the village community. Judging from the results of calculating the correlation coefficient value for the three variables, it reached 0.912 or 91.2%, where this value is included in the very strong category. This proves that the dissemination of digital literacy and information through the social media Facebook of community leaders for the residents of the Canal village is very effective.